1999
DOI: 10.1177/002246699903300302
|View full text |Cite
|
Sign up to set email alerts
|

Ecobehavioral Assessment in Early Childhood Programs

Abstract: The purpose of this investigation was to describe the nature of preschool children's experiences in inclusive early childhood programs. The momentary time-sampling data reported in this article represented 3 hours of observational information per child for 112 preschoolers with and without disabilities in 16 community-based, inclusive preschool programs in four states. In general, children with and without disabilities exhibited similar child behaviors and were meaningfully engaged in a variety of adult- and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
1
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 28 publications
2
63
1
6
Order By: Relevance
“…An eco-behavioural observational system, called the CASPER II, has been designed to collect information about preschool environments and the behaviour of children and adults within those environments. It consists of seven ecological variables and provides information about child behaviour, child social behaviour, and adult behaviour (Brown, Odom, Li, & Zercher, 1999).…”
Section: Direct Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…An eco-behavioural observational system, called the CASPER II, has been designed to collect information about preschool environments and the behaviour of children and adults within those environments. It consists of seven ecological variables and provides information about child behaviour, child social behaviour, and adult behaviour (Brown, Odom, Li, & Zercher, 1999).…”
Section: Direct Observationmentioning
confidence: 99%
“…An eco-behavioural observational system, called the CASPER II, has been designed to collect information about preschool environments and the behaviour of children and adults within those environments. It consists of seven ecological variables and provides information about child behaviour, child social behaviour, and adult behaviour (Brown, Odom, Li, & Zercher, 1999).The OSRAC-P coding system was initially developed in 2002. It is a combination of three different observational systems, 1) the CARS, 2) the CASPER II, and 3) the Observational System for the Environmental Determinants of Physical Activity in Preschool Children Study (Brown et al, 2009c).…”
mentioning
confidence: 99%
“…Despite the evidence that many young children with disabilities have at least one friend, observations in inclusive preschool classrooms provide consistent evidence that children with disabilities are included in social interactions with their peers less frequently than are children without disabilities (cf., Brown, Odom, Li, & Zercher, 1999;Guralnick et al, 1996). Odom and colleagues found that a substantial proportion of young children with disabilities were at risk for explicit rejection by the peer group.…”
mentioning
confidence: 99%
“…As other studies explained (Fine, 1981;Brown et al, 1999), children's difficulty to form autonomous relations has implications for their peerrelated social competence since an important step in socialization is children's increasing ability to interact with peers and spend more time in settings in which adults are not present to enforce their views of mannered interaction.…”
Section: Discussionmentioning
confidence: 96%